Deteksi Kecurangan Laporan Keuangan Pada Perusahaan Sektor Farmasi dengan Beneish M-Score - Pratama, Muhammad Naufal Putra; Aminah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This research seeks to identify the potential for fraudulent activities in the financial statements of companies operating within the pharmaceutical industry that are listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Fraudulent financial reporting can diminish public confidence and have detrimental effects on the economy. The study utilizes the Beneish M-Score method, which evaluates the probability of manipulation in financial statements through ratio analysis. A total of 11 pharmaceutical firms participated in this research and were classified into Non-Manipulator, Grey Company, and Manipulator categories based on the conducted ratio analysis. The results showed an increase in the number of companies classified as Non Manipulators and Manipulators from year to year, while the Gray Company category showed fluctuations. This study provides insight into the prevalence of financial statement fraud in the pharmaceutical sector and suggests the need for stricter supervision to prevent fraudulent practices.